Kriteria E-Learning Untuk Pembelajaran SMA/MA Berdasarkan Quality Matters Rubric (QMR) K-12 - Shintia Putri Riski; Relsas Yogica (Departement of Mathematics Education, 2023)
E-learning is one of the innovations in education that is widely used. The quality of E-learning greatly influences the quality of learning. This article aims to describe good e-learning criteria for high school/MA online learning according to the Quality Matters Rubric (QMR) K-12 standard. The research was conducted using the library research method with content analysis data analysis techniques. The results show that good E-learning for learning based on QMR must meet certain specified standards. This standard is divided into 8 general standards: general description & introduction, objectives and competencies, assessment & measurement, teaching materials, learning activities & student interaction, technology, student & teacher support, and accessibility and usability. General standards are divided into several special standards that explain in more detail related to general standards.